2013
DOI: 10.1371/journal.pgen.1003940
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between NSL Histone Acetyltransferase and MLL/SET Complexes: NSL Complex Functions in Promoting Histone H3K4 Di-Methylation Activity by MLL/SET Complexes

Abstract: hMOF (MYST1), a histone acetyltransferase (HAT), forms at least two distinct multiprotein complexes in human cells. The male specific lethal (MSL) HAT complex plays a key role in dosage compensation in Drosophila and is responsible for histone H4K16ac in vivo. We and others previously described a second hMOF-containing HAT complex, the non-specific lethal (NSL) HAT complex. The NSL complex has a broader substrate specificity, can acetylate H4 on K16, K5, and K8. The WD (tryptophan-aspartate) repeat domain 5 (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 41 publications
(63 reference statements)
2
43
1
Order By: Relevance
“…41 The DPY-30 protein is homologous to human protein hDPY-30, which is a member of the COMPASS complex. 42 In light of the reported co-ordination of NSL and COMPASS complex activity in humans noted above, 26 it is of interest that we also demonstrated a direct interaction between DPY-30 and both SUMV-1 and SUMV-2 using yeast two-hybrid assays. 34 The common phenotype of synMuv suppression, combined with evidence of physical association, suggests that DPY-30 might facilitate a functional interaction between the nematode COMPASS complex and putative NSL complex.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…41 The DPY-30 protein is homologous to human protein hDPY-30, which is a member of the COMPASS complex. 42 In light of the reported co-ordination of NSL and COMPASS complex activity in humans noted above, 26 it is of interest that we also demonstrated a direct interaction between DPY-30 and both SUMV-1 and SUMV-2 using yeast two-hybrid assays. 34 The common phenotype of synMuv suppression, combined with evidence of physical association, suggests that DPY-30 might facilitate a functional interaction between the nematode COMPASS complex and putative NSL complex.…”
mentioning
confidence: 63%
“…23 Interestingly, coordinated activity of the NSL and COMPASS complexes has been proposed, with WDR5 acting as a bridge between the two. 26 Recently, however, it has been reported that the interaction of WDR5 with NSL complex components occurs via the same regions with which WDR5 interfaces with COMPASS complex components, suggesting that the two interactions are mutually exclusive.…”
Section: O-linkedmentioning
confidence: 99%
“…Our study shows that MOF blocks H3K4 demethylation by LSD1. Moreover, the NSL complex shares common subunits with the MLL H3K4 methyltransferase complexes (Cai et al, 2010;Dias et al, 2014;Dou et al, 2005;Li et al, 2009;Mendjan et al, 2006;Sharma et al, 2010;Zhao et al, 2013b). Therefore, in addition to implementing H4K16 acetylation, MOF may promote H3K4 methylation by dissociating the LSD1 demethylase and engaging the MLL methyltransferase, thereby driving the transition from a transcription-repressed state to an active state.…”
Section: Discussionmentioning
confidence: 99%
“…However, while the structure of the WDR5 b-propeller domain and its ability to bind H3, the WIN motif, and RbBP5 within MLL complexes are well documented, it remains unclear how WDR5 presents itself within other complexes, such as NSL or ATAC. WDR5 was proposed to be a bridging or crossshared subunit between the NSL and MLL/COMPASS complexes, forming complexes with both histone methyltransferase and acetyltransferase activities (Dou et al 2005;Li et al 2009;Zhao et al 2013b). However, we and others could not confirm the existence of such a complex (Cai et al 2010;Raja et al 2010).…”
mentioning
confidence: 99%